Pilot testing an intervention to educate and promote nutritious choices at food pantries - McKee, Sarah L.; Gurganus, Eminet Abebe; Atoloye, Abiodun T.; Xu, Ran; Martin, Katie; Schwartz, Marlene B. (Journal of public health, 2023)
Aim This study aimed to assess the impact of the Supporting Wellness at Pantries (SWAP) system on client food selections at a food pantry. Subject and methods In a pre–post comparison study design, a client-choice food pantry implemented SWAP by reorganizing its inventory to promote healthy options. Each product was ranked as “choose often” (green), “sometimes” (yellow), or “rarely” (red) based on saturated fat, sodium, and sugar. Signage was added to indicate each item’s SWAP rank and healthier foods were placed at eye level. Client food baskets were assessed at time 1 ( n = 121) and time 2 ( n = 101). The proportions of green and red foods selected were compared using regression analyses. Results The regression analyses showed that the proportion of green foods selected by clients increased by 11% ( p < 0.001) and the proportion of red foods selected decreased by 7% ( p < 0.001) after SWAP was implemented ( n = 222). Conclusions SWAP has the potential to positively shift client choices among the items available in a food pantry setting. SWAP is one component of a suite of changes to the charitable food system that have the potential to alleviate food insecurity, improve diet quality, and assist clients in managing diet-related diseases.